1980
DOI: 10.1002/jez.1402130211
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of primary mesenchyme cell ingression in the sea urchin Lytechinus pictus

Abstract: The ultrastructural changes associated with primary mesenchyme cell formation in the sea UrchinLytechinuspictus were studied by transmission (TEM) and scanning electron microscopy (SEM). Early during ingression, one can recognize about 30 presumptive primary mesenchyme cells, which form a ring around eight central cells, located at the apex of the vegetal pole. The first steps involve the loss of the basal lamina in the vegetal plate region and the loss of cilia from the 30 presumptive primary mesenchyme cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
72
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 16 publications
3
72
1
Order By: Relevance
“…PKCrelated break down of inositol phospholipids occurs in association with desmosomes (Kitajima et al, 1992), the intercellular junction also found in sea urchin ectoderm (Katow and Solursh, 1980). Thus, desmosomes could be involved in the present intercellular propagation of [Ca 2+ ] i elevation in the ciliary epithelium.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…PKCrelated break down of inositol phospholipids occurs in association with desmosomes (Kitajima et al, 1992), the intercellular junction also found in sea urchin ectoderm (Katow and Solursh, 1980). Thus, desmosomes could be involved in the present intercellular propagation of [Ca 2+ ] i elevation in the ciliary epithelium.…”
Section: Discussionmentioning
confidence: 80%
“…However, since ectodermal cells are less than 1/10 of the diameter of an oocyte [about 110·m and often the subject of [Ca 2+ ] i wave propagation studies (e.g. Kyozuka et al, 1998) from the previous cell to the next through gap junctions (Braet et al, 2003) also seems to be an unlikely mechanism in sea urchin larvae, because gap junctions were not found in the ectoderm (Katow and Solursh, 1980), and connexin-like proteins have not been found in the Sea Urchin Genome Resources to date (Sea Urchin Genome Sequencing Consortium, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…2). [6][7][8][9][10] The major model species have consisted of Hemicentrotus pulcherrimus in Japan, Strongylocentrotus purpuratus and Lytechinus variegatus in North America, and Paracentrotus lividus in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Two of 3 NMC genes, Hp-ecpn 6 and Hp-gad, 5 are expressed in the ectoderm as early as the 15-hpf swimming blastula stage until at least the 2-arm pluteus stage in H. pulcherrimus. The Hp-ECPN expressing cells (ECPN cells) plays an essential role in photoresponsive larval swimming.…”
mentioning
confidence: 99%
“…These nascent PMCs ingress through the basal lamina and migrate into the blastocoele (for details, see Katow and Solursh, 1980) (reviewed by Solursh, 1986). During EMT, the PMCs downregulate cell-cell adhesion (Fink and McClay, 1985), increase motility, change cell shape, and finally become mesenchymal cells with a migratory behavior.…”
Section: Introductionmentioning
confidence: 99%